The Promise of Character Education in Middle School: A Meta-Analysis - Calvary R Diggs; Patrick Akos (Middle Grades Review, 2016)
Early adolescence is a developmental stage characterized by changes in reasoning, social cognition, and desire for autonomy in youth aged 11-14 (or grades 6-8). This period is also associated with heightened impulsivity and risk-taking that has been linked to school-related challenges such as antisocial behaviors and declining grades. Character education, a particular brand of social-emotional practice, has been promulgated as a developmentally responsive program that can promote prosocial behavior and academic success by building upon existing developmental strengths. However, research findings to date are primarily informed by elementary school program outcomes. Due to this limitation, a meta-analytic review of recent research on middle school character education programs and interventions was completed. Findings demonstrate positive associations between character education and academic and behavioral success, as well as social and internal perceptions.
Keywords: character education; meta-analysis; middle school; social-emotional learning